Mechanism, prevention and treatment of cognitive impairment caused by high altitude exposure - Chen, Xin; Zhang, Jiexin; Lin, Yuan; Li, Yan; Wang, Han; Wang, Zhanhao; Liu, Huawei; Hu, Yonghe; Liu, Lei (Frontiers in Physiology, 2023)
High altitude hypobaric hypoxia (HH) characteristics induce impaired cognitive function, reduced concentration, and memory. In recent years, an increasing number of people have migrated to highaltitude areas for work and study. The high-altitude sickness from HH, such as hHeadache, vomiting, sleep disturbance, and cognitive impairment from HH, severely challenges the physical and mental health and affects their quality of life and work efficiency. This review summarizes the manifestations, mechanisms, and preventive and therapeutic methods of high altitude HH environment affecting cognitive function and provides theoretical references for exploring and treating high altitude-induced cognitive impairment.